DETERMINATION OF THE ANGULAR COORDINATES OF ASTRONOMICAL OBJECTS: DETERMINATION OF THE ANGULAR COORDINATES OF ASTRONOMICAL OBJECTS - Getsov, Petar; Zhekov, Zhivko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Among the methods for angular coordinates determination of the astronomical objects, particularly a topic of the present day is the Turner method based on static processing of data information for three and more stars number. With regard to used in astronomical practice optical electronic apparatuses which have high resolution and comparatively closely a field of vision lower than one degree of Celsius, it grows up the actuality of the methods for angular coordinates determination at minimum number of supporting (catalogue) stars. In this conditions it’s necessary to be re-examine the respect to orthogonality methods, the accuracy of which can be increase through statistical analyze. Calculation for ideal coordinates and the equatorial coordinates of an astronomical object are shown as well as the possible errors for their determination. A priori it is supposed the orthogonality method is more effective because of the fact that the possibility for appearance in the two stars field of vision is bigger than of the three ones.